Vol. 2337 : Thermophysical Basis of Energy Technologies (TBET 2020) proceedings of IX All-Russian scientific conference with international participation, Tomsk, Russia, October 28-30, 2020 - Kuznetsov G. V. Geny Vladimirovich; Feoktistov D. V. Dmitriy Vladimirovich; Orlova E. G. Evgeniya Georgievna (2021, 2021)
Title screen